The impact of preoperative language mapping by repetitive navigated transcranial magnetic stimulation on the clinical course of brain tumor patients - Sollmann, Nico; Ille, Sebastian; Hauck, Theresa; Maurer, Stefanie; Negwer, Chiara; Zimmer, Claus; Ringel, Florian; Meyer, Bernhard; Krieg, Sandro M (BMC cancer, 2015)
Background Language mapping by repetitive navigated transcranial magnetic stimulation (rTMS) is used for resection planning in patients suffering from brain lesions within regions known to be involved in language function. Yet we also need data that show whether patients benefit clinically from preoperative rTMS for language mapping. Methods We enrolled 25 patients with language eloquently located brain lesions undergoing preoperative rTMS language mapping (GROUP 1, 2011–2013), with the mapping results not being available for the surgeon, and we matched these patients with 25 subjects who also underwent preoperative rTMS (GROUP 2, 2013–2014), but the mapping results were taken into account during tumor resection. Additionally, cortical language maps were generated by analyzing preoperative rTMS and intraoperative direct cortical stimulation (DCS) data. Results Mean anterior-posterior (ap) craniotomy extents and overall craniotomy sizes were significantly smaller for the patients in GROUP 2 (Ap: p = 0.0117; overall size: p = 0.0373), and postoperative language deficits were found significantly more frequently for the patients in GROUP 1 (p = 0.0153), although the preoperative language status did not differ between groups (p = 0.7576). Additionally, there was a trend towards fewer unexpected tumor residuals, shorter surgery duration, less peri- or postoperative complications, shorter inpatient stay, and higher postoperative Karnofsky performance status scale (KPS) for the patients in GROUP 2. Conclusions The present study provides a first hint that the clinical course of patients suffering from brain tumors might be improved by preoperative rTMS language mapping. However, a significant difference between both groups was only found for craniotomy extents and postoperative deficits, but not for other clinical parameters, which only showed a trend toward better results in GROUP 2. Therefore, multicenter trials with higher sample sizes are needed to further investigate the distinct impact of rTMS language mapping on the clinical course of brain tumor patients.